The emergence of the quantified child. Issue 5 (3rd September 2017) - Smith, Rebecca
ABSTRACT: Using document analysis, this paper examines the historical emergence of the quantified child, revealing how the collection and use of data has become normalized through legitimizing discourses. First, following in the traditions of Foucault's genealogy and studies examining the sociology of numbers, this paper traces the evolution of data collection in a range of significant education policy documents. Second, a word count analysis was used to further substantiate the claim that data collection and use has been increasingly normalized through legitimizing discourses and routine actions in educational settings. These analyses provide evidence that the need to quantify educational practices has been justified over long periods of time through a variety of documents and that the extent to which data governs educators' thoughts, discourses, and actions has dramatically increased during the past century.